2016 IEEE 59th International Midwest Symposium on Circuits and Systems (MWSCAS) 2016
DOI: 10.1109/mwscas.2016.7870020
|View full text |Cite
|
Sign up to set email alerts
|

A nafion coated capacitive humidity sensor on a flexible PET substrate

Abstract: This paper reports a simple and low-cost technique for fabricating low-power capacitive humidity sensors without the use of a cleanroom environment. A maskless laser engraving system was utilized to fabricate two different gold electrode structures, interdigitated electrodes and Hilbert's fifth-order fractal. The capacitive structures were implemented on a flexible PET substrate. The usage of Nafion, a well-known polymer for its hydrophilic properties as a sensing film, was attempted on the PET and outperforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…At 100 kHz and above, there were negligible reductions in the sensitivity of the device. The increase in sensitivity is because a lower drive frequency provides a longer time for the polarization of the adsorbed acetone [ 81 ]. However, at lower frequencies, the response is relatively noisier because of the larger drift and fluctuation in the output response of the sensor, affecting the LOD as well as the short- and long-term stability of the sensor.…”
Section: Resultsmentioning
confidence: 99%
“…At 100 kHz and above, there were negligible reductions in the sensitivity of the device. The increase in sensitivity is because a lower drive frequency provides a longer time for the polarization of the adsorbed acetone [ 81 ]. However, at lower frequencies, the response is relatively noisier because of the larger drift and fluctuation in the output response of the sensor, affecting the LOD as well as the short- and long-term stability of the sensor.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, extreme conditions of humidity have adverse effects on human health and are linked to many diseases . Different types of humidity sensors have been developed based on either solid-state devices, , flexible substrates, inkjet printed textile, or textile fiber composite materials. , Most of these studies demonstrated the sensitivity of the sensor; however, only a few of these discussed the selectivity of the sensor, which is equally important. Moreover, in the case of textile-based humidity sensors, to the best of our knowledge, there is no report describing the selectivity of the textile sensors in the presence of interferences such as volatile organic compounds (VOCs).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, PET has a high humidity resistance, therefore, it is generally more used in applications where the device is exposed to a high humidity environments. [62]…”
Section: Mechanical Propertiesmentioning
confidence: 99%